ANALISIS KINERJA KEUANGAN ECONOMIC VALUE ADDED (EVA) PADA PT. PEGADAIAN (PERSERO) KANTOR WILAYAH II PEKANBARU - Ulfa Desti Youlanda; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to analyze the financial performance at PT. Pegadaian (Persero) Pekanbaru Regional Office II with the Economic Value Added method during the 2014-2018 period. The subject in this research is PT. Pegadaian (Persero) Pekanbaru Regional Office II and the object of this research is the Financial Statements for the 2014-2018 period which already includes balance sheet report posts and income statements. The data collection method used in this research is documentation. The data analysis method used in this study is analysis with Economic Value Added (EVA) with the time series method. Based on the research results, it is known that the company's financial performance is quite good because it has achieved a positive value and has produced economic added value in certain 3 years, experiencing a slight decrease in the value of EVA in certain 2 years. The value becomes positive because the level of capital costs is lower than the rate of return on the company's operating profit. Keywords: Financial Performance, Economic Value Added (EVA), Capital Cost Level, and Operating Profit Return Rate.